Investigation of Wave Overtopping from Various Geometrical Configurations of Coastal Breakwater Ramps - Azlan Musa, Mohd; Fadhli Ahmad, Mohammad; Aieni Mokhtar, Nor; Jusoh, Ahmad (International Journal of Engineering and Technology, 2018)
Breakwater is often required for erosion protection. The effectiveness of breakwater structure as a coastal defence could be determined through overtopping wave surpass onto its crest freeboard structure. The common design practice of breakwater structure is using a linear ramp configuration. There is still a limited knowledge on the contribution of various configuration ramps shape into breakwater efficiency. Thus, this study attempts to investigate a few other's configuration of ramp geometries through overtopping discharge rate performance and identified its relationships with the crest freeboard. Three configurations of ramp geometries (convex, concave and cubic) have been investigated using numerical simulation of CFD-Flow 3D software. The result indicates that, there are significant influences of ramp configuration parameters on the overtopping rate and the highest overtopping rate is contributed from cubic shape ramp geometry. It is recommended that the detail study on cubic ramp shape geometry for determining its capability in increasing overtopping rate.
Keywords: Overtopping Wave; Breakwater Ramp; CFD-FLOW3D.